2008
DOI: 10.1111/j.1365-294x.2007.03628.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast phylogeography of Dipentodon (Dipentodontaceae) in southwest China and northern Vietnam

Abstract: The evolutionary history of plants in the southeast Tibetan Plateau might be the most complicated around the world because of the area's extremely complex topography and climate induced by strong tectonic activity in recent history. In this research, we implemented a phylogeographical study using chloroplast sequences (psbA-trnH and trnQ-rps16 intergenic spacer) on Dipentodon, a monotypic or ditypic genus (D. sinicus and D. longipedicellatus) distributed in southwest China and adjacent areas including Myanmar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 51 publications
4
72
1
Order By: Relevance
“…These geologic/geographic barriers may have limited the expansion of the species and may have played an important role in forming a rough ''Tanaka Line'' (Tanaka 1954, Fig. 1) (a boundary between the SinoJapanese plate/biogeographic region in the east and the Sino-Himalayan plate/biogeographic region in the west, approximately corresponding to a straight line starting at 28°N, 98°E and progressing southward to approximately 18°45 0 or 19°N, 108°E) distribution pattern for M. cathcartii; a distribution pattern that also occurs for many other Sino-Himalayan taxa (e.g., Caryota urens Linn, Taiwania cryptomerioides Hayata, Dipentodon sinicus Dunn and Tacca chantrieri André) in Yunnan Province (Li and Li 1992;Zhang et al 2006a;Yuan et al 2008). …”
Section: Levels Of Genetic Variation Within and Among Populationsmentioning
confidence: 95%
“…These geologic/geographic barriers may have limited the expansion of the species and may have played an important role in forming a rough ''Tanaka Line'' (Tanaka 1954, Fig. 1) (a boundary between the SinoJapanese plate/biogeographic region in the east and the Sino-Himalayan plate/biogeographic region in the west, approximately corresponding to a straight line starting at 28°N, 98°E and progressing southward to approximately 18°45 0 or 19°N, 108°E) distribution pattern for M. cathcartii; a distribution pattern that also occurs for many other Sino-Himalayan taxa (e.g., Caryota urens Linn, Taiwania cryptomerioides Hayata, Dipentodon sinicus Dunn and Tacca chantrieri André) in Yunnan Province (Li and Li 1992;Zhang et al 2006a;Yuan et al 2008). …”
Section: Levels Of Genetic Variation Within and Among Populationsmentioning
confidence: 95%
“…This region harbours about 12,000 species of vascular plants, of which at least 20 genera and 3,500 species are endemic (Myers et al 2000;Wang and Zhang 1994;Wilson 1992;Wu 1988;Ying et al 1993). Previous studies of plant phylogeography in this region have focused mainly on taxa from the plateau areas of the Qinghai-Tibetan Plateau and adjacent mountain ranges (e.g., the Hengduan Mountains) (Yuan et al 2008;Zhang et al 2007aZhang et al , 2005. However, from a phylogeographic perspective, far less attention has been devoted to the endemic flora of the valleys of the region, e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Each individual island may have acted as a microfuge during glaciation. A majority of phylogeographic research in this region have demonstrated that the unique topography promoted strong population structure, independent refugial isolation and locally endemic speciation (Liu et al 2009;Wang et al 2008;Yuan et al 2008). In the cases of our results, significant phylogeographic structures were inferred from cpDNA in P. tunicoides and P. secundiflora, as one conclusion, the region probably provided sheltering for these species.…”
Section: Population Genetic Structurementioning
confidence: 96%